Clozapine-Induced Pneumonitis: A Case Report - Torrico, Tyler; Crandall, Ronald O.; Meza, Carlos; Abdijadid, Sara (Frontiers in Psychiatry, 2020)
Introduction: Clozapine is the most effective antipsychotic used for treatment resistant schizophrenia and recurrent suicidal behavior in schizophrenia or schizoaffective disorder. However, it has been underutilized due to its adverse reaction profile. Although clozapine is typically associated with neutropenia leading to increased risk of infection (i.e. pneumonia), there have been a few case reports of non-neutropenic, non-infectious drug-induced lung disease (i.e. pneumonitis). Although pneumonia and pneumonitis may have similar clinical presentation, their etiology, management, and treatment are different. Case Presentation: A 53-year-old African American female with schizoaffective disorder was hospitalized for grave disability. The patient developed a sepsis-like presentation during clozapine titration which resolved after treatment for presumed pneumonia and clozapine discontinuation. When clozapine was resumed due to persistent psychosis, the patient again developed a sepsis-like presentation. Clozapine was again discontinued with no other interventions and the patient’s symptoms resolved. Conclusions: Drug-induced pneumonitis is a very rare adverse reaction of clozapine. Recognizing conditions that mimic sepsis may prevent patients from undergoing unnecessary laboratory testing and prevent exposure to unwarranted antibiotics.